ELATIHAN CARA PENYIAPAN MAKANAN YANG SEHAT DAN AMAN: TEKNIK KOMPLEMENTER MEMANF AATKAN BAHAN MAKANAN LOKAL BAGI PENGELOLA TPA - Yuliati, Yuliati -; Rahayu, Tutiek (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
This   public    service    program    aims   to   provide    some    knowledge     and   skill improvement   on selecting  and preparing  children  foods  using  complementary   technique, and some  knowledge   improvement   on composing  children  food menu.  It is expected  that after  this  program   the  participants   will  be  able  to  design  models   and  menu   lists  of children  food  menu  using  complementary     technigue   for nutritious   substance  especially protein. Although   the food price  is reduced, the nutritious  content  is better.  Moreover,  the children    cared   are   protected    from   food   poisoning,    malnutrition    and   improve    the awareness  of selecting  healthy  foods in children  as early as possible.The  method   applied  in  this  program   was  lecture,  discussion   and  practical   work simulation. The   presentation    of   the   group   practical    work   was   in   the   form   of   a competition. The duration  of this program  was 33 hours.  Participants  were delegated  from10 children  involving   19 representatives.The    program  was conducted  from  20 June to  12November  2002.The  results  show  that  most  of the  participants   comment  that  this  training  is very useful   in  improving   cooking   activity  in  childeares.It is  found  that  the  competition model  motivates   the  participants   to  actively  attend  the  program.   The  evaluation   thus shows that  84,3%  of the participants  achieve  good result while the rest ( 15,7%)   are in the average.  Generally,  the participants   ( 77,7%  ), before  the training  did not know  the concepts   of  preparing   healthy  and  safe  foods.In   order  to  improve  protein  nutritious value   of  food,   participantas,    presented   24  main   dishes   (  8  lauk   and   16  sayur   ) composed  in menu  lists for 30 days using complementary  technique.   Key words:   Complementary   technique.